Laminated high-temperature adhesive for connecting aluminum oxide and titanium alloy and preparation method of laminated high-temperature adhesive
Through the stacked high-temperature adhesive technology, the problem of thermal stress relief between alumina and titanium alloys in high temperature environments is solved, and a high-strength and heat-resistant connection effect is achieved, which is suitable for aerospace and other fields.
Patent Information
- Application Number
- CN202411581598.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-25
AI Technical Summary
The thermal mismatch and thermal expansion differences between alumina and titanium alloys are large, resulting in easy cracking of the connection parts under high temperature environments, and it is difficult for existing high-temperature bonding technology to effectively alleviate thermal stress.
Using a laminated high-temperature adhesive, the base glue and intermediate layer glue are applied on the bonding surface between alumina and titanium alloy, and the bonding parts with a multi-layer structure are formed by drying and calcining from room temperature to high temperature to relieve thermal stress and improve bonding strength.
The high-strength connection between alumina and titanium alloy is realized, and it can maintain considerable connection strength within the temperature range from room temperature to 1000°C. It is simple to operate and environmentally friendly, and is suitable for high-temperature environments.
Smart Images

Figure CN119684906A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesive material preparation, and particularly relates to a laminated high-temperature adhesive for connecting aluminum oxide and titanium alloy and a preparation method thereof. Background Art
[0002] Alumina ceramics, with their high hardness and high temperature resistance, are the preferred materials for manufacturing thermal protection systems and engine components. In the field of aerospace, the use of alumina ceramics ensures the stability of the structure at high temperatures and is a key material for protecting flight safety. Titanium alloys, with their high strength, light weight, high temperature resistance and corrosion resistance, have become important materials in the aerospace field. Under extreme conditions, it can maintain performance while ensuring the stability of the structure, and is widely used in key components of aircraft and rockets, such as fuselages and engine blades. In recent years, alumina and titanium alloy connectors have received great attention in the installation and fixation of the hot end of hypersonic aircraft. The combination of alumina and titanium alloys achieves the goal of lightweight structure and functional optimization, and significantly improves system performance and reliability. Whether it is high-energy physics experiments, military equipment, or civil engineering, they are widely used and show great potential.
[0003] Due to the huge difference in physical and chemical properties between ceramics and alloys, how to break through the limitation of thermal performance mismatch to achieve the connection between the two is the primary technical problem. Due to the harsh service environment, how to ensure that the connection parts do not crack under the action of cold and hot cycles, hot air flow scouring, and high-temperature multi-stress impact is another technical difficulty. Among the many connection methods, welding technologies such as brazing are the main means to achieve high-strength connection between ceramics and alloys. However, since titanium alloy structural parts are relatively light and thin and have limited temperature resistance, the instantaneous high temperature introduced during welding can easily damage the components. Therefore, seeking alternative non-destructive connections is the key to preparing alumina and titanium alloy connectors. Compared with welding methods, high-temperature adhesive bonding technology does not require the use of any equipment. Once applied and cured, it can be directly used in a high-temperature environment without damaging the bonding parts. It is easy to operate, has high connection efficiency, high specific strength, and is applicable to a variety of objects, which provides ideas for new connections between alumina and titanium alloys.
[0004] However, high-temperature bonding technology also faces the challenge of large differences in thermal expansion between alumina and titanium alloys. How to overcome the difference in thermal expansion between materials and develop high-temperature adhesives that can provide excellent heat resistance, anti-aging properties and good bonding strength for alumina and titanium alloys has become a key technical breakthrough in the field of heterogeneous material connection. Conventional single-layer high-temperature adhesives (or single-layer bonding methods) are difficult to alleviate the thermal stress caused by the large difference in thermal expansion, resulting in limited bonding effects. Laminated materials have excellent thermal stress relief effects, which provides ideas for the research and development of laminated high-temperature adhesives and matching laminated bonding methods. The laminated high-temperature adhesive and its preparation method provided by the present invention are important breakthroughs in achieving high-strength connections between alumina and titanium alloys. Summary of the invention
[0005] In order to solve the above problems, the object of the present invention is to provide a laminated high-temperature adhesive for connecting aluminum oxide and titanium alloy and a preparation method thereof.
[0006] To achieve the above object, the present invention provides the following technical solution: a laminated high-temperature adhesive for connecting aluminum oxide and titanium alloy and a preparation method thereof, which specifically comprises the following steps:
[0007] (1) adding water to 85% concentrated phosphoric acid to adjust the concentration to about 55-65% to obtain dilute phosphoric acid;
[0008] (2) Weigh the diluted phosphoric acid, aluminum hydroxide, and zirconium hydroxide prepared in step (1) in a mass ratio of 4-5:0.5-1:0.5-1 and place them separately. Stir the diluted phosphoric acid in a constant temperature water bath at 70-75°C, and slowly add the aluminum hydroxide and zirconium hydroxide into the diluted phosphoric acid in sequence while stirring. After the powder is completely dissolved, mechanically stir the mixed solution at a speed of 400-600 r / min. After stirring is complete, a milky white aluminum zirconium phosphate gel-based liquid is obtained;
[0009] (3) Silicon powder, boron carbide, titanium powder, nickel powder, alumina and the aluminum zirconium phosphate colloid liquid prepared in step (2) are weighed in sequence according to a mass ratio of 13.5-14.5:5.5-6.5:4.5-6.5:4.5-6.5:20.5-21.5:45-50, and they are placed in a mortar for preliminary mixing to ensure that the colloid reaches a highly uniform state, thereby obtaining a high-temperature adhesive 1 (primer) specially used for connecting alumina and titanium alloy.
[0010] (4) Weigh the diluted phosphoric acid, aluminum hydroxide, and zirconium hydroxide prepared in step (1) in order according to a mass ratio of 7.5-9.5:0.5-1.5:2-3, and place them separately. Stir the diluted phosphoric acid in a constant temperature water bath at 70-75°C, and slowly add aluminum hydroxide and zirconium hydroxide to the diluted phosphoric acid in turn while stirring. After the powder is completely dissolved, mechanically stir the mixed solution at a speed of 400-600 r / min, and after stirring is complete, a milky white aluminum zirconium phosphate gel-based liquid is obtained;
[0011] (5) Silicon powder, boron carbide, aluminum oxide and the aluminum zirconium phosphate colloid liquid prepared in step (4) are placed in a mortar in a mass ratio of 2-3:0.5-1.5:4.5-6.5:15.5-17 for preliminary mixing, and ground until the powder disappears completely to ensure that the colloid reaches a highly uniform state, thereby obtaining a high-temperature adhesive 2 (intermediate layer adhesive) specially used for connecting aluminum oxide and titanium alloy.
[0012] (6) The special high-temperature adhesive 1 (primer) prepared in step (3) is brushed on the bonding surfaces of aluminum hydroxide and titanium alloy respectively, and then the thickness of the high-temperature adhesive 1 (primer) on each bonding surface is controlled to be 200-500 μm with a coater; the aluminum oxide and titanium alloy coated with the high-temperature adhesive 1 (primer) are dried and cured at room temperature to 80° C. for 20-60 min, and after curing, they are placed in a high-temperature furnace and calcined at 700-1000° C. for 0.5-1 h.
[0013] (7) The high temperature adhesive 2 (intermediate layer adhesive) prepared in step (5) is brushed on the adhesive surfaces of the aluminum oxide and titanium alloy prepared in step (6), and the thickness of the high temperature adhesive is controlled to be 100-300 μm by using an applicator; the aluminum oxide and titanium alloy coated with the high temperature adhesive 2 (intermediate layer adhesive) are bonded together with the bonding surfaces facing each other to form a bonded part, and then the aluminum oxide and titanium alloy bonded parts are pressurized and dried for 2-6 hours in the range of room temperature to 80°C. The formed aluminum oxide / titanium alloy heterogeneous material bonded parts can be directly used in high temperature environments and have considerable connection strength in the range of room temperature to 1000°C.
[0014] Preferably, in step (1), the concentrated phosphoric acid is analytical grade with a purity higher than 98%; the water in step (1) can be from any water source and has no effect on the process.
[0015] Preferably, in step (2) and step (4), the purity of aluminum hydroxide is higher than 99%, and the particle size is 10-25 μm; the purity of zirconium hydroxide is higher than 99%, and the particle size is 6-15 μm; the zirconium-aluminum phosphate colloid liquid prepared in step (2) and step (4) has a different zirconium-aluminum ratio and cannot be interchanged or confused.
[0016] Preferably, in step (3) and step (5), the particle size of the elemental silicon powder is 0.5-5 μm, the particle size of the boron carbide powder is 6-10 μm, and the purity of both is higher than 99%; the particle size of the titanium powder is 1-25 μm, the particle size of the nickel powder is 1-5 μm, and the purity of both is higher than 98%; the particle size of the alumina is 0.5-5 μm, and the purity is higher than 99%.
[0017] Preferably, the thickness of the high temperature adhesive 1 (primer) applied in step (6) should be strictly controlled and should not be too thick, otherwise the primer surface will crack. In addition, the adhesive can be pre-treated at high temperature using a flame spray gun after applying the primer, which can improve construction efficiency.
[0018] Preferably, the laminated bonded part after curing in step (7) can also be pre-treated in the range of 700-1000° C., so that the strength of the bonded part is higher.
[0019] The laminated high-temperature adhesive for connecting aluminum oxide and titanium alloy provided by the present invention and the preparation method thereof have the following beneficial effects:
[0020] 1. The preparation process is simple, green and pollution-free, using renewable materials as raw materials, and meets the requirements of environmental protection and sustainable development;
[0021] 2. High temperature adhesive can provide bonding strength of more than 4MPa for the connection of alumina and titanium alloy in the temperature range of 700-900℃, and can reach up to 6.45MPa;
[0022] 3. The thermal expansion coefficient of high temperature adhesive 2 (intermediate layer adhesive) is 6.13×10 -6 K -1 , while the highest thermal expansion coefficient of high temperature adhesive 1 (primer) is 8.37×10 -6 K -1 , which can achieve a gradient matching of the thermal expansion coefficient of the adhesive layer, can help alleviate thermal stress and improve the reliability of the connection part;
[0023] 4. The adhesive layer achieves close contact with the interface, maintains a highly compatible interface steady state with the substrate, and ensures that the bonding strength remains stable under a wide range of temperature changes without significant performance degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is the shear strength curve of the aluminum oxide and titanium alloy laminate bonded component prepared in Example 1 measured at room temperature after being treated at different temperatures;
[0025] Figure 2 is a test force-displacement curve of the aluminum oxide and titanium alloy laminate bonded component prepared in Example 1 subjected to a shear test at room temperature after being treated at 900°C;
[0026] Figure 3 is the XRD spectrum of the high temperature adhesive 1 (primer) prepared in Example 1 after being treated at 800°C;
[0027] Figure 4 is the XRD spectrum of the high temperature adhesive 1 (primer) prepared in Example 1 after being treated at 1000°C;
[0028] Figure 5 is the XRD spectrum of the high temperature adhesive 2 (intermediate layer adhesive) prepared in Example 1 after being treated at 800°C;
[0029] Figure 6 is the XRD spectrum of the high temperature adhesive 2 (intermediate layer adhesive) prepared in Example 1 after being treated at 1000°C;
[0030] Figure 7 1 is the thermal expansion curve of the high temperature adhesive 1 (primer) prepared in Example 1 after heat treatment at 800°C.
[0031] Figure 8This is the thermal expansion curve of the high temperature adhesive 2 (intermediate layer adhesive) prepared in Example 1 after heat treatment at 800°C. DETAILED DESCRIPTION
[0032] The present invention will be further described below in conjunction with specific embodiments.
[0033] Example 1
[0034] The present embodiment provides a laminated high-temperature adhesive for connecting aluminum oxide and titanium alloy and a preparation method thereof, comprising the following steps performed in sequence:
[0035] (1) adding water to 85% concentrated phosphoric acid to adjust the concentration to about 55% to obtain dilute phosphoric acid;
[0036] (2) Weigh the diluted phosphoric acid, aluminum hydroxide, and zirconium hydroxide prepared in step (1) in order according to a mass ratio of 16:1:1, and place them separately. Stir the diluted phosphoric acid in a constant temperature water bath at 70°C, and slowly add the aluminum hydroxide and zirconium hydroxide into the diluted phosphoric acid in order while stirring. After the powder is completely dissolved, mechanically stir the mixed solution at a speed of 400 r / min, and after stirring is complete, a milky white aluminum zirconium phosphate gel-based liquid is obtained;
[0037] (3) Silicon powder, boron carbide, titanium powder, nickel powder, aluminum oxide and the aluminum zirconium phosphate colloid liquid prepared in step (2) were weighed in order according to a mass ratio of 13.5:5.5:4.5:4.5:20.5:95, and they were placed in a mortar for preliminary mixing to ensure that the colloid reached a highly uniform state, thereby obtaining a high-temperature adhesive 1 (primer) specially used for connecting aluminum oxide and titanium alloy;
[0038] (4) Weigh the diluted phosphoric acid, aluminum hydroxide, and zirconium hydroxide prepared in step (1) in order according to a mass ratio of 15:1:4 and place them separately. Stir the diluted phosphoric acid in a constant temperature water bath at 70°C, and slowly add the aluminum hydroxide and zirconium hydroxide into the diluted phosphoric acid in order while stirring. After the powder is completely dissolved, mechanically stir the mixed solution at a speed of 400 r / min. After stirring is complete, a milky white aluminum zirconium phosphate gel-based liquid is obtained;
[0039] (5) Silicon powder, boron carbide, aluminum oxide and the aluminum zirconium phosphate colloid liquid prepared in step (4) are placed in a mortar in a mass ratio of 4:1:9:31, and mixed in sequence, and ground until the powder disappears completely to ensure that the colloid reaches a highly uniform state, thereby obtaining a high-temperature adhesive 2 (intermediate layer adhesive) for connecting aluminum oxide and titanium alloy;
[0040] (6) The special high-temperature adhesive 1 (primer) prepared in step (3) is brushed on the bonding surfaces of aluminum oxide and titanium alloy, and then the thickness of the high-temperature adhesive 1 (primer) on each bonding surface is controlled to 200 μm by using an applicator; the aluminum oxide and titanium alloy coated with the high-temperature adhesive 1 (primer) are dried and cured at room temperature for 20 minutes, and after curing, they are placed in a high-temperature furnace and calcined at 900° C. for 0.5 hours;
[0041] (7) The high temperature adhesive 2 (intermediate layer adhesive) prepared in step (5) is brushed on the adhesive surfaces of the aluminum oxide and titanium alloy prepared in step (6), and the thickness of the high temperature adhesive is controlled to 100 μm by using an applicator; the aluminum oxide and titanium alloy coated with the high temperature adhesive 2 (intermediate layer adhesive) are bonded together with the bonding surfaces facing each other to form a bonded part, and then the aluminum oxide and titanium alloy bonded parts are pressurized, dried and cured at room temperature for 2 hours. The formed aluminum oxide / titanium alloy heterogeneous material bonded parts can be directly used in high temperature environments and have considerable connection strength in the range of room temperature to 1000°C.
[0042] Example 2
[0043] The present embodiment provides a laminated high-temperature adhesive for connecting aluminum oxide and titanium alloy and a preparation method thereof, comprising the following steps performed in sequence:
[0044] (1) adding water to 85% concentrated phosphoric acid to adjust the concentration to about 60% to obtain dilute phosphoric acid;
[0045] (2) Weigh the diluted phosphoric acid, aluminum hydroxide, and zirconium hydroxide prepared in step (1) in a mass ratio of 4:1:1 and place them separately. Stir the diluted phosphoric acid in a constant temperature water bath at 70°C, and slowly add the aluminum hydroxide and zirconium hydroxide into the diluted phosphoric acid in sequence while stirring. After the powder is completely dissolved, mechanically stir the mixed solution at a speed of 500 r / min. After stirring is complete, a milky white aluminum zirconium phosphate gel-based liquid is obtained;
[0046] (3) Weigh silicon powder, boron carbide, titanium powder, nickel powder, aluminum oxide and the aluminum zirconium phosphate colloid base liquid prepared in step (2) in a mass ratio of 14:6:6:6:21:47, place them in a mortar and mix them preliminarily to ensure that the colloid reaches a highly uniform state, and prepare a high-temperature adhesive 1 (primer) specially used for connecting aluminum oxide and titanium alloy;
[0047] (4) Weigh the diluted phosphoric acid, aluminum hydroxide, and zirconium hydroxide prepared in step (1) in order according to a mass ratio of 8:1:2.5 and place them separately. Stir the diluted phosphoric acid in a constant temperature water bath at 70°C, and slowly add the aluminum hydroxide and zirconium hydroxide into the diluted phosphoric acid in order while stirring. After the powder is completely dissolved, mechanically stir the mixed solution at a speed of 500 r / min. After stirring is complete, a milky white aluminum zirconium phosphate gel-based liquid is obtained;
[0048] (5) Silicon powder, boron carbide, aluminum oxide and the aluminum zirconium phosphate colloid liquid prepared in step (4) are placed in a mortar in a mass ratio of 2:1:5:16, and mixed in sequence, and ground until the powder disappears completely to ensure that the colloid reaches a highly uniform state, thereby obtaining a high-temperature adhesive 2 (intermediate layer adhesive) for connecting aluminum oxide and titanium alloy;
[0049] (6) The special high-temperature adhesive 1 (primer) prepared in step (3) is brushed on the bonding surfaces of aluminum oxide and titanium alloy, and then the thickness of the high-temperature adhesive 1 (primer) on each bonding surface is controlled to 300 μm by using an applicator; the aluminum oxide and titanium alloy coated with the high-temperature adhesive 1 (primer) are dried and cured at room temperature to 80° C. for 30 min, and after curing, they are placed in a high-temperature furnace and calcined at 1000° C. for 0.5 h;
[0050] (7) The high temperature adhesive 2 (intermediate layer adhesive) prepared in step (5) is brushed on the adhesive surfaces of the aluminum oxide and titanium alloy prepared in step (6), and the thickness of the high temperature adhesive is controlled to 100 μm by using an applicator; the aluminum oxide and titanium alloy coated with the high temperature adhesive 2 (intermediate layer adhesive) are bonded together with the bonding surfaces facing each other to form a bonded part, and then the aluminum oxide and titanium alloy bonded parts are pressurized, dried and cured at room temperature for 4 hours. The formed aluminum oxide / titanium alloy heterogeneous material bonded parts can be directly used in high temperature environments and have considerable connection strength in the range of room temperature to 1000°C.
[0051] Example 3
[0052] The present embodiment provides a laminated high-temperature adhesive for connecting aluminum oxide and titanium alloy and a preparation method thereof, comprising the following steps performed in sequence:
[0053] (1) adding water to 85% concentrated phosphoric acid to adjust the concentration to about 65% to obtain dilute phosphoric acid;
[0054] (2) Weigh the diluted phosphoric acid, aluminum hydroxide, and zirconium hydroxide prepared in step (1) in a mass ratio of 5:1:1 and place them separately. Stir the diluted phosphoric acid in a constant temperature water bath at 75°C, and slowly add the aluminum hydroxide and zirconium hydroxide into the diluted phosphoric acid in sequence while stirring. After the powder is completely dissolved, mechanically stir the mixed solution at a speed of 600 r / min. After stirring is complete, a milky white aluminum zirconium phosphate gel-based liquid is obtained;
[0055] (3) Silicon powder, boron carbide, titanium powder, nickel powder, aluminum oxide and the aluminum zirconium phosphate colloid liquid prepared in step (2) were weighed in sequence according to a mass ratio of 14.5:6.5:6.5:6.5:21.5:50, and they were placed in a mortar for preliminary mixing to ensure that the colloid reached a highly uniform state, thereby obtaining a high-temperature adhesive 1 (primer) for connecting aluminum oxide and titanium alloy;
[0056] (4) Weigh the diluted phosphoric acid, aluminum hydroxide, and zirconium hydroxide prepared in step (1) in a mass ratio of 9.5:1.5:3 and place them separately. Stir the diluted phosphoric acid in a constant temperature water bath at 75°C, and slowly add aluminum hydroxide and zirconium hydroxide into the diluted phosphoric acid in sequence while stirring. After the powder is completely dissolved, mechanically stir the mixed solution at a speed of 600 r / min. After stirring is complete, a milky white aluminum zirconium phosphate gel-based liquid is obtained;
[0057] (5) Silicon powder, boron carbide, aluminum oxide and the aluminum zirconium phosphate colloid liquid prepared in step (4) are placed in a mortar in a mass ratio of 3:1.5:6.5:17, and mixed in sequence, and ground until the powder disappears completely to ensure that the colloid reaches a highly uniform state, thereby obtaining a high-temperature adhesive 2 (intermediate layer adhesive) for connecting aluminum oxide and titanium alloy;
[0058] (6) The special high-temperature adhesive 1 (primer) prepared in step (3) is brushed on the bonding surfaces of aluminum oxide and titanium alloy, and then the thickness of the high-temperature adhesive 1 (primer) on each bonding surface is controlled to 500 μm by using an applicator; the aluminum oxide and titanium alloy coated with the high-temperature adhesive 1 (primer) are dried and cured at 80° C. for 60 min, and after curing, they are placed in a high-temperature furnace and calcined at 700° C. for 1 h;
[0059] (7) The high temperature adhesive 2 (intermediate layer adhesive) prepared in step (5) is brushed on the adhesive surfaces of the aluminum oxide and titanium alloy prepared in step (6), and the thickness of the high temperature adhesive is controlled to 300 μm by using an applicator; the aluminum oxide and titanium alloy coated with the high temperature adhesive 2 (intermediate layer adhesive) are bonded together with the bonding surfaces facing each other to form a bonded part, and then the aluminum oxide and titanium alloy bonded parts are pressurized and dried at 80°C for 6 hours. The formed aluminum oxide / titanium alloy heterogeneous material bonded parts can be directly used in high temperature environments and have considerable connection strength in the range of room temperature to 1000°C.
[0060] The high-temperature adhesive provided by the present invention is specifically used for the connection between alumina and titanium alloy. Its matrix is an aluminum zirconium phosphate adhesive base liquid obtained by the reaction of phosphoric acid with aluminum hydroxide and zirconium hydroxide. The prepared alumina and titanium alloy bonding parts have the ability to maintain excellent bonding strength and mechanical properties in a high-temperature environment from room temperature to 1000°C, and can be directly used in a high-temperature environment. The thermal expansion of high-temperature adhesive 1 (base adhesive) is higher than that of high-temperature adhesive 2 (intermediate layer adhesive). The stacked three-layer combination of the two can achieve a thermal expansion gradient combination of the adhesive layer, which can be beneficial in alleviating thermal stress. The aluminum-zirconium ratio of the two adhesives is different, which can affect the amount of zirconium oxide generated, thereby regulating the thermal expansion of the adhesive layer. Both adhesives contain silicon powder and boron carbide, which can produce volume compensation during the oxidation process, thereby maintaining the structural integrity of the adhesive layer. At the same time, the two can further react with other components in the adhesive to generate high-temperature resistant components, thereby improving the heat resistance of the adhesive. Compared with high temperature adhesive 2 (intermediate layer adhesive), high temperature adhesive 1 (primer adhesive) contains certain metal components (aluminum, titanium, nickel), which can react to form intermetallic compounds at high temperatures, thereby increasing the thermal expansion of high temperature adhesive 1 (primer adhesive). In short, this connection method can keep the colloid stable in a high temperature environment, effectively prevent structural damage caused by thermal expansion and contraction, and increase its service life under extreme conditions.
[0061] In order to verify the use effect of the high temperature adhesive provided in the above embodiment, the inventors conducted the following experiments:
[0062] 1) Preparation of aluminum oxide and titanium alloy laminated bonding parts: aluminum oxide and titanium alloy laminated connecting parts were prepared according to the embodiment method of the present invention. The prepared bonding parts were obtained after the high-temperature adhesive 2 (intermediate layer adhesive) was cured without other temperature pretreatment.
[0063] 2) High temperature calcination treatment: The prepared alumina and titanium alloy laminated adhesive was calcined at different temperatures (100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C) for 1 hour. In addition, high temperature adhesive 1 (primer) and high temperature adhesive 2 (intermediate layer adhesive) were also heat treated separately at the above different temperatures.
[0064] 3) Normal temperature shear test: The shear strength of the laminated bonded parts of aluminum oxide and titanium alloy after being treated at different temperatures was tested using a CSS-44001 universal testing machine. The bonding strength of the laminated high temperature adhesive was evaluated through comparative experiments. Figure 1 At the same time, the test force-displacement curve of the shear test at room temperature after 900℃ treatment is recorded, as shown in Figure 2 shown.
[0065] Depend on Figure 1It can be seen that the laminated high-temperature adhesive can also provide a bonding strength of not less than 3MPa for the connection between aluminum oxide and titanium alloy in the processing temperature range of 100-400°C; the bonding strength in the processing temperature range of 500-600°C is maintained at about 3MPa. And it can provide a bonding strength of not less than 4MPa or even up to nearly 6.45MPa at 700-900°C. It can be seen that the laminated high-temperature adhesive for connecting aluminum oxide and titanium alloy prepared by the present invention has excellent bonding performance.
[0066] Depend on Figure 2 It can be seen that the test force-displacement curve of the bonded part drops sharply after reaching the highest point, indicating that the adhesive has brittle fracture and high stiffness, which is consistent with the characteristics of ceramics.
[0067] 4) Adhesive composition analysis: The components of the high temperature adhesive 1 (primer adhesive) and the high temperature adhesive 2 (intermediate layer adhesive) prepared in the embodiment after being treated at different temperatures were analyzed using an XRD tester (D / Max 2500v / PC, Rigaku). The XRD spectra of the high temperature adhesive 1 (primer adhesive) after being treated at 800°C and 1000°C are as follows: Figure 4 and Figure 5 As shown; the XRD spectrum of high temperature adhesive 2 (intermediate layer adhesive) after being treated at 800℃ and 1000℃ is as follows Figure 5 and Figure 6 shown.
[0068] according to Figure 3 and Figure 4 XRD spectrum analysis shows that after treatment at 800℃, Al2O3, Zr2P2O7, AlPO4, Ni 0.5 The formation of ceramic phases such as TiOPO4, SiO2, ZrB2, and nickel-zirconium intermetallic compounds, these heat-resistant substances indicate that the high-temperature adhesive has a certain thermal stability and can adapt to the needs of high-temperature environments. When the treatment temperature rises to 1000°C, the intermetallic compounds and residual metal components are completely oxidized or reacted, and more ceramic products are generated in the high-temperature adhesive, including ZrO2, AlB2, TiO2, and Al(PO3)3. At this point, the temperature resistance of the high-temperature adhesive is further improved. At the same time, due to the high thermal expansion coefficients of ZrO2 and TiO2 (8.5-10.5×10 -6 K -1 ), which are the key to the high thermal expansion coefficient of high temperature adhesive 1 (primer).
[0069] according to Figure 5 and Figure 6According to the XRD spectrum analysis, after treatment at 800℃, only ceramic phases such as Al2O3, ZrP2O7 and AlPO4 appeared in the high temperature adhesive 2 (intermediate layer adhesive); as the temperature rises to 1000℃, more phosphate ceramic phases appear in the high temperature adhesive 2 (intermediate layer adhesive). Although ZrO2 is also generated, phosphates with a smaller thermal expansion coefficient are the majority, which is an important reason why the intermediate layer adhesive of the high temperature adhesive (2) has a lower thermal expansion coefficient.
[0070] 5) Thermal expansion performance analysis: The thermal expansion coefficient curves of the high temperature adhesive 1 (primer adhesive) and the high temperature adhesive 2 (intermediate layer adhesive) prepared in the embodiment after heat treatment at 800°C were tested using a German NETZSCH DIL 402C thermal mechanical analysis equipment. Figure 7 , Figure 8 shown.
[0071] from Figure 7 From the above, the thermal expansion coefficient of high temperature adhesive 1 (primer) increases rapidly in the low temperature range and reaches a stable value at around 200°C, which is 8.37×10 -6 K -1 Near the 0.05°C, as the temperature further increases, its thermal expansion coefficient remains basically constant, indicating good thermal stability in a higher temperature range. This shows that the adhesive will have a more obvious expansion reaction during the transition from low temperature to medium temperature, but exhibits stable characteristics at high temperatures.
[0072] Figure 8 When the temperature of the high temperature adhesive 2 (intermediate layer adhesive) is raised to about 200°C, the thermal expansion coefficient also increases rapidly, but reaches about 6.13×10 -6 K -1 After that, it tends to be stable and is always lower than the expansion coefficient of high temperature adhesive 1. This means that the thermal expansion reaction of high temperature adhesive 2 (intermediate layer adhesive) is relatively mild and is more suitable for applications under conditions with low thermal expansion change requirements.
Claims
1. A laminated high temperature adhesive for connecting aluminum oxide and titanium alloy and a preparation method thereof, characterized in that: The laminated high-temperature adhesive for connecting aluminum oxide and titanium alloy and the preparation method thereof include the following steps performed in sequence: (1) adding water to 85% concentrated phosphoric acid to adjust the concentration to about 55-65% to obtain dilute phosphoric acid; (2) Weigh the diluted phosphoric acid, aluminum hydroxide, and zirconium hydroxide prepared in step (1) in a mass ratio of 4-5:0.5-1:0.5-1 and place them separately. Stir the diluted phosphoric acid in a constant temperature water bath at 70-75°C, and slowly add the aluminum hydroxide and zirconium hydroxide into the diluted phosphoric acid in sequence while stirring. After the powder is completely dissolved, mechanically stir the mixed solution at a speed of 400-600 r / min. After stirring is complete, a milky white aluminum zirconium phosphate gel-based liquid is obtained; (3) Silicon powder, boron carbide, titanium powder, nickel powder, alumina and the aluminum zirconium phosphate colloid liquid prepared in step (2) are weighed in sequence according to a mass ratio of 13.5-14.5:5.5-6.5:4.5-6.5:4.5-6.5:20.5-21.5:45-50, and they are placed in a mortar for preliminary mixing to ensure that the colloid reaches a highly uniform state, thereby obtaining a high-temperature adhesive 1 (primer) specially used for connecting alumina and titanium alloy. (4) Weigh the diluted phosphoric acid, aluminum hydroxide, and zirconium hydroxide prepared in step (1) in order according to a mass ratio of 7.5-9.5:0.5-1.5:2-3, and place them separately. Stir the diluted phosphoric acid in a constant temperature water bath at 70-75°C, and slowly add aluminum hydroxide and zirconium hydroxide to the diluted phosphoric acid in turn while stirring. After the powder is completely dissolved, mechanically stir the mixed solution at a speed of 400-600 r / min, and after stirring is complete, a milky white aluminum zirconium phosphate gel-based liquid is obtained; (5) Silicon powder, boron carbide, aluminum oxide and the aluminum zirconium phosphate colloid liquid prepared in step (4) are placed in a mortar in a mass ratio of 2-3:0.5-1.5:4.5-6.5:15.5-17 for preliminary mixing, and ground until the powder disappears completely to ensure that the colloid reaches a highly uniform state, thereby obtaining a high-temperature adhesive 2 (intermediate layer adhesive) specially used for connecting aluminum oxide and titanium alloy. (6) The special high-temperature adhesive 1 (primer) prepared in step (3) is brushed on the bonding surfaces of aluminum hydroxide and titanium alloy respectively, and then the thickness of the high-temperature adhesive 1 (primer) on each bonding surface is controlled to be 200-500 μm with a coater; the aluminum oxide and titanium alloy coated with the high-temperature adhesive 1 (primer) are dried and cured at room temperature to 80° C. for 20-60 min, and after curing, they are placed in a high-temperature furnace and calcined at 700-1000° C. for 0.5-1 h. (7) The high temperature adhesive 2 (intermediate layer adhesive) prepared in step (5) is brushed on the adhesive surfaces of the aluminum oxide and titanium alloy prepared in step (6), and the thickness of the high temperature adhesive is controlled to be 100-300 μm by using an applicator; the aluminum oxide and titanium alloy coated with the high temperature adhesive 2 (intermediate layer adhesive) are bonded together with the bonding surfaces facing each other to form a bonded part, and then the aluminum oxide and titanium alloy bonded parts are pressurized, dried and cured for 2-6 hours in the range of room temperature to 80°C. The formed aluminum oxide / titanium alloy heterogeneous material bonded parts can be directly used in high temperature environments and have considerable connection strength in the range of room temperature to 1000°C.
2. The laminated high-temperature adhesive for connecting aluminum oxide and titanium alloy and the preparation method thereof according to claim 1, characterized in that: In step (1), the concentrated phosphoric acid is analytical grade with a purity higher than 98%. The water in step (1) can be from any water source and has no effect on the process.
3. The laminated high-temperature adhesive for connecting aluminum oxide and titanium alloy and the preparation method thereof according to claim 1, characterized in that: In step (2) and step (4), the purity of aluminum hydroxide is higher than 99%, and the particle size is 10-25 μm; the purity of zirconium hydroxide is higher than 99%, and the particle size is 6-15 μm; the zirconium aluminum phosphate colloid liquid prepared in step (2) and step (4) has a different zirconium to aluminum ratio and cannot be interchanged or confused.
4. The laminated high-temperature adhesive for connecting aluminum oxide and titanium alloy and the preparation method thereof according to claim 1, characterized in that: In step (3) and step (5), the particle size of the elemental silicon powder is 0.5-5 μm, the particle size of the boron carbide powder is 6-10 μm, and the purity of both is higher than 99%; the particle size of the titanium powder is 1-25 μm, and the particle size of the nickel powder is 1-5 μm, and the purity of both is higher than 98%; the particle size of the aluminum oxide is 0.5-5 μm, and the purity is higher than 99%.
5. The laminated high temperature adhesive for connecting aluminum oxide and titanium alloy and the preparation method thereof according to claim 1, characterized in that: In step (6), the thickness of the high temperature adhesive 1 (primer) should be strictly controlled and should not be too thick, otherwise it will easily cause the primer surface to crack. In addition, the bonded parts can also be pre-treated with a flame spray gun at high temperature after applying the primer, which can improve construction efficiency.
6. The laminated high temperature adhesive for connecting aluminum oxide and titanium alloy and the preparation method thereof according to claim 1, characterized in that: The laminated bonded part cured in step (7) may also be pre-treated at a temperature in the range of 700-1000° C., which can increase the strength of the bonded part.